PENGARUH MODEL PEMBELAJARAN PENDIDIKAN MATEMATIKA REALISTIK INDONESIA (PMRI) BERBANTUAN MEDIA KONKRET TERHADAP PEMAHAMAN KONSEP MATEMATIKA - Maunah, Khayatul; Retnaningsih , Rahayu; Sukiyanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research aims to determine the effect of using the Indonesian Realistic Mathematics Education Model (PMRI) assisted by concrete object media on the understanding of mathematical concepts in class III students at SD Negeri Banjarsari, Windusari District, Magelang Regency. This research is a type of quasi-experimental research (Quasi Experimental Research), while the research design uses Nonequivalent Control Group Design. The research population was all class III students at Banjarsari State Elementary School, totaling 44 III A and III B students. The sample in this study was students consisting of 24 class III A students as the experimental class and 20 class III B students as the control class. The sample was obtained using total sampling technique where the researcher used the entire population as a sample. The data collection method in this research uses a urian test which has gone through a validity and reliability testing process. The data analysis technique uses Paired Sample T-test, the normality of which has previously been determined. The results of the analysis show that there is a difference in the average post-test score, namely using the Indonesian Realistic Mathematics Learning Model (PMRI) assisted by concrete object media of 85.83 with the highest score of 96.49 and the lowest score of 63.33, while the control class uses conventional methods with an average post-test score of 57.83 with the highest score of 86.67 and the lowest score of 36.67. This is reinforced by the results of hypothesis testing using the Paired Sample T-Test in pair 1 showing a significance value of 0.000 <0.05 so it can be concluded that there is a difference in the average understanding of mathematical concepts in the pre-test and post-test scores of the experimental class using the Indonesian Realistic Mathematics (PMRI) model assisted by concrete object media. Meanwhile, Pair 2 shows a significance value of 0.230 > 0.05 so it can be concluded that there is no difference in the average understanding of mathematical concepts in the pre-test and post-test scores for the Control class using the conventional model (lecture). From these results it can be concluded that the use of the Indonesian Realistic Mathematics Education Learning Model (PMRI) assisted by concrete object media has a positive influence on the understanding of mathematical concepts in class III of Banjarsari State Elementary School, WIndusari District, Magelang Regency.